Numerical investigation of the influence of particle size and particle number ratios on texture and force transmission in binary granular composites - P. Jongchansitto (2018)
© 2016 Elsevier B.V. The morphology of two-dimensional bidisperse composite granular materials without cohesion is statistically analyzed in terms of geometrical texture and force transmission. The effects of both the particle number and the particle size ratios are evidenced by comparing twenty different composite samples simulated by molecular dynamics. The samples are composed of two constitutive materials with a stiffness ratio of about four between stiff and soft particles. By changing the D stiff /D soft ratio in the range of 1.2–3.0 and the N stiff /N soft ratio in the range of 0.1–1.0, the results under confined vertical compression show that the coordination number for the whole set of contacts slightly changes with the particle number and particle size ratios. When we consider contact sub-networks, the contacts between stiff particles orient parallel to the axis of compression, while the soft-soft and stiff-soft contacts play a vital role in maintaining the equilibrium of the granular system by sustaining the stiff-stiff contacts. Interestingly, normal force distributions are characterized by an exponential decay for the strong network, and a power-law for the weak network. Nearly 60% of the total number of contacts belong to the weak network. Finally, experimental data obtained recently by thermoelastic stress analysis and numerical results obtained in the present study are in good agreement in terms of the distributions of the hydrostatic stresses and the contact directions.